2016
DOI: 10.1186/s40900-016-0035-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in patient safety research: a workshop to review patient information, minimise psychological risk and inform research

Abstract: Plain English summaryPatient safety is a growing research area. However, although patients and the public are increasingly involved in clinical research, there is little guidance on how best to involve patients in patient safety research. Here we focus on how patients can contribute to the design of patient safety research.We conducted a workshop with patients as part of a project exploring errors and safety in the delivery of intravenous medication (medication given via a vein). The workshop was designed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…As found in earlier research, pain associated with cannulation was described as an unpleasant experience ( 9 , 10 ). In line with previous work, this study also highlighted that pump alarms can be a significant source of patient concern ( 7 ) and cause discomfort in preventing patients from sleeping ( 9 ). As has been widely reported in health-care research ( 15 ), the role of the health-care professional, in this study primarily nurses, was very important in providing a positive patient experience.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As found in earlier research, pain associated with cannulation was described as an unpleasant experience ( 9 , 10 ). In line with previous work, this study also highlighted that pump alarms can be a significant source of patient concern ( 7 ) and cause discomfort in preventing patients from sleeping ( 9 ). As has been widely reported in health-care research ( 15 ), the role of the health-care professional, in this study primarily nurses, was very important in providing a positive patient experience.…”
Section: Discussionsupporting
confidence: 89%
“…An interview topic guide (Supplementary Material) was developed based on relevant literature and the earlier patient involvement workshop (7) to explore patients’ views on issues and activities relating to the administration of intravenous infusions. Demographic data were collected in the form of patients’ year of birth and ethnic background.…”
Section: Methodsmentioning
confidence: 99%
“…PPI workshops will be organised in Birmingham and London before the main study period, with a focus on designing the study adapting the model from an earlier project (the 'before' study is reported by Furniss et al). 18…”
Section: Dissemination Of Resultsmentioning
confidence: 99%
“…PPI will extend to consultation on dissemination and outreach activities and involvement with data analysis and interpretation, using models employed previously. 45 46 All PPI will occur remotely, compliant with current public health advice for avoiding face-to-face contact. Our PPI partners will be offered the opportunity to coauthor the future papers describing our research findings.…”
Section: Methods and Analysismentioning
confidence: 99%